Analisis Kinerja Agro-Eduwisata PT. Hidroponik Padjadjaran Indonesia melalui Pendekatan Balanced Scorecard: Analysis of Agroedutourism Performance PT. Hidroponik Padjadjaran Indonesia through Balanced Scorecard Approach - Thoriq, Ahmad Thoriq; Amayu, Kharista; Pratopo, Lukito Hasta; Perwitasari, Sophia Dwiratna Nur; Septiningsih, Ratna Dwi (Jurnal Agroekoteknologi dan Agribisnis, 2024)
One of the business units of PT Hidroponik Padjadjaran Indonesia is engaged in Agroedutourism. The main income from this business is hydroponic education and training activities. The problem to be examined is that in recent years there has been a fluctuation in the number of visitors and training participants. This study aims to analyze the performance of agroedutourism at PT Hidroponik Padjadjaran Indonesia. In this research balanced scorecard approach is used which is based on financial, customer, internal business process, and learning perspectives. The results of the study indicate that from the financial perspective, the Return on Asset (ROA) value is 0,25 percent per year, Return on Equity (ROE) is 10,57 percent per year and the Net Profit Margin (NPM) value is 44 percent per year. From the consumer perspective, the Customer Satisfaction Index (CSI) value is 80 percent of consumers who are satisfied with the company's performance. From the learning perspective, with the results of 73,93 percent employees are satisfied with the company's performance. Morover from the internal business perspective, it is known that there are two innovative products produced that support the company's performance. The financial perspective show that ROA value is below the standard. The solution to improve the business performance is to provide intense service and promotion directly to schools in surrounding area as well as training to improve capacity building for employee.